2009
DOI: 10.1016/j.febslet.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent regulation of muscle caveolin activation and insulin signalling in response to high‐fat diet

Abstract: a b s t r a c tWe studied the effect of high-fat diet on the expression and activation of the three caveolins in rat skeletal muscle and their association with the insulin signalling cascade. Initial response was characterized by increased signalling through Cav-1 and Cav-3 phosphorylation, suggesting that both participate in an initial acute response to the calorie surplus. Afterwards, Cav-1 signalling was slightly reduced, whereas Cav-3 remained active. Late chronic phase signalling through both proteins was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
6
6
0
Order By: Relevance
“…In the current study, we demonstrated that cardiomyocyte Cav-3 expression increased 6–12 h after HG exposure but reduced to basal levels within 24 h and progressively further reduced to lower than basal levels after 36–48 h of HG exposure. The initial increase in Cav-3 expression after HG exposure observed in our study is an acute response to the calorie surplus similar to that reported by other researchers (40). The significant reduction of Cav-3 expression in cardiomyocytes after prolonged HG exposure is consistent with our results from the intact rats, which showed that Cav-3 expression was decreased in isolated cardiomyocytes from rats of 8- and 5-week duration of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we demonstrated that cardiomyocyte Cav-3 expression increased 6–12 h after HG exposure but reduced to basal levels within 24 h and progressively further reduced to lower than basal levels after 36–48 h of HG exposure. The initial increase in Cav-3 expression after HG exposure observed in our study is an acute response to the calorie surplus similar to that reported by other researchers (40). The significant reduction of Cav-3 expression in cardiomyocytes after prolonged HG exposure is consistent with our results from the intact rats, which showed that Cav-3 expression was decreased in isolated cardiomyocytes from rats of 8- and 5-week duration of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…As previously reported using the same dietary model [17], body and adipose depot weights of the animals fed on the HF-diet were significantly higher than those fed on the control diet. However, no differences were found between the fasted (F) and non-fasted (NF) groups of animals (Table 1).…”
Section: Resultssupporting
confidence: 81%
“…In a late phase, after a prolonged time feeding on a high-fat diet, insulin resistance becomes apparent, accompanied by an impairment of Cav-3 and Cav-1 in skeletal muscle [17], whereas in adipocytes, Cav-1 and Cav-2 expression are increased, together with an inhibition of insulin signalling intermediaries [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that when the cardiomyocytes were exposed to high glucose for a long time (48 h), expression of Cav-3 decreased significantly. However, some studies showed that when the myocardial cells were exposed to high glucose for a short duration (6-12h), expression of Cav-3 in myocardial cells increased [28]. It is believed that the myocardial cells regulate the expression of Cav-3 as the acute stress reaction for self-protection when being exposed to high glucose.…”
Section: Discussionmentioning
confidence: 99%